2013
DOI: 10.3109/14397595.2013.862352
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of nicotine on collagen-induced arthritis and on the induction and function of in vitro-cultured Th17 cells

Abstract: Nicotine stimulation attenuated signs and severity of arthritis in mice. Activation of nicotine acetylcholine receptors on in vitro-cultured Th17 cells decreased their pro-inflammatory function, which may play a potential role in alleviating arthritis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Stimulation of the a7nAChR with nicotine or AR-R17779 resulted in reduced clinical arthritis scores and decreased expression of TNF [40]. Other studies confirmed these results using the a7nAChR agonist GTS-21 (also known as dimethoxybenzylidene anabaseine, DMBX-A) or nicotine [40,[61][62][63]. Conversely, unilateral dissection of the vagus nerve resulted in a trend towards increased arthritis activity in animal models of arthritis which did not reach statistical significance, possibly due to the relatively small number of animals tested [40,62].…”
Section: Influence Of the Autonomic Nervous System On Chronic Inflammsupporting
confidence: 73%
“…Stimulation of the a7nAChR with nicotine or AR-R17779 resulted in reduced clinical arthritis scores and decreased expression of TNF [40]. Other studies confirmed these results using the a7nAChR agonist GTS-21 (also known as dimethoxybenzylidene anabaseine, DMBX-A) or nicotine [40,[61][62][63]. Conversely, unilateral dissection of the vagus nerve resulted in a trend towards increased arthritis activity in animal models of arthritis which did not reach statistical significance, possibly due to the relatively small number of animals tested [40,62].…”
Section: Influence Of the Autonomic Nervous System On Chronic Inflammsupporting
confidence: 73%
“…The cholinergic anti-inflammatory pathway is the efferent or motor arm of the "inflammatory reflex", the neural circuit that responds to and regulates the inflammatory response (15). In the neural circuit, the neurotransmitter endogenic acetylcholine, for example, can interact with the receptors expressed on immune cells and thus alter immune cell function (16). It is generally acknowledged that acetylcholine can bind to the integral membrane protein as acetylcholine receptors, including nicotinic acetylcholine receptors (nAChR) and muscarinic acetylcholine receptors (mAChR).…”
Section: Nicotine and Inflammationmentioning
confidence: 99%
“…Until day 35, the nicotine group significantly suppressed histological IL-17A, serum TNFa, and pro-inflammatory cytokines IL-17A and IL-6 mRNA expression in isolated splenocytes. Furthermore, isolated CD4 + IL-17A + Th17 cells expressing a7 nAChR stimulated by nicotine may decrease their pro-inflammatory function (16). Nicotine was added to drinking water (100 mg/ml, about 300 mg nicotine per day per mouse) for male DBA/1 mice from the day of immunization by chicken collagen II, resulting in a delay in arthritis.…”
Section: Anti-inflammatory Effect Of Nicotine On Arthritismentioning
confidence: 99%
“…For example, nicotinic agonists induce T-helper cells shift to a Th2 anti-inflammatory phenotype [75]. Nicotine can also inhibit inflammation in arthritis by reducing IL-17 production by splenic α7nAChR-expressing Th17 cells [76], or preventing macrophage infiltration into the synovial tissues by inhibiting the expression of adhesion molecules such as ICAM-1 [77]. Indeed, RA was originally considered a Th1-mediated disease due to the high levels of TNF and IFN-γ and the lack of Th2-cytokines such as IL-4.…”
Section: Pharmacological Translation For Arthritismentioning
confidence: 99%